Analysis of Management Information System Utilization for Learning Outcome Evaluation and Student Welfare Enhancement - Rohman, M Kholilur (Al-Qalam Institue, 2023)
This study aims to analyze the use of Management Information Systems (MIS) in evaluating learning outcomes and its implications for student welfare in Madrasah Aliyah. This study departs from the challenges faced by teachers and students in managing academic data and learning evaluations that are still carried out manually. The conventional evaluation process often affects administrative efficiency and the quality of interaction between teachers and students. Thus, the implementation of MIS is expected to improve evaluation efficiency, administrative accuracy, and provide a positive impact on student learning motivation and welfare. This study uses a qualitative approach with a descriptive type, combining data collection techniques in the form of interviews, observations, and documentation to explore the perspectives of teachers and students on the use of MIS. The results of the study indicate that the implementation of MIS can improve efficiency in the evaluation process, reduce administrative errors, and accelerate the provision of feedback to students. In addition, MIS also contributes to increasing student learning motivation, because they can quickly identify their shortcomings and make improvements before the final exam. This study is expected to provide an important contribution in describing how technology can improve the quality of learning and student welfare, especially in the madrasah environment, as well as provide recommendations for the development of more optimal educational technology infrastructure in Islamic schools.